2003
DOI: 10.1093/ps/82.6.1008
|View full text |Cite
|
Sign up to set email alerts
|

Molting and Salmonella enterica serovar enteritidis infection: the problem and some solutions

Abstract: Induced molting is an important economic tool used by the egg industry to recycle an aging layer flock. It is estimated that approximately 70% of the flocks nationwide and almost 100% in California are molted annually. Considering that there are approximately 240 million hens in production in the U.S., a rough estimate of the numbers of hens molted every year would be between 144 and 168 million birds, a substantial number. There are many methods to induce molt, but feed removal until hens lose a specific weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 19 publications
1
57
1
5
Order By: Relevance
“…For example, the most prevalent molt strategy in the USA is feed removal until hens lose a specific weight. However, hens molted in this way were found to be 100-to 1 000-fold more susceptible to infection by S. Enteritidis and excreted significantly higher numbers in their faeces [75]. Several authors reported that the major risk factors were related to disinfection, hygiene barriers and feedmill [37,69].…”
Section: Farm Practicesmentioning
confidence: 99%
“…For example, the most prevalent molt strategy in the USA is feed removal until hens lose a specific weight. However, hens molted in this way were found to be 100-to 1 000-fold more susceptible to infection by S. Enteritidis and excreted significantly higher numbers in their faeces [75]. Several authors reported that the major risk factors were related to disinfection, hygiene barriers and feedmill [37,69].…”
Section: Farm Practicesmentioning
confidence: 99%
“…Moulted birds in T 4 showed greater (P<0.01) percentage loss in body weight (15.41%), than those of moulted hens in T 1 (6.03%) and T 2 (7.17%). The percentage weight loss of moulted hens in T 3 (11.93%) was intermediate among the treatments.…”
Section: Moulting Periodmentioning
confidence: 85%
“…For instance, researchers and public health authorities have identified the method as a significant risk factor for the infection of laying flocks with Salmonella enteritidis; the most important pathogen inside eggs, and known to be transmitted to humans [3]. Many researchers also subscribed that the practice of feed withdrawal is inhumane, and should be handled with upmost caution [4][5][6]. As an alternative to fasting laying hens as a method of inducing moult, several studies have advocated a non-feed withdrawal method, involving the manipulation of dietary minerals like sodium, calcium, iodine and zinc [6][7][8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Molting induced by fasting may compromise the immune system of laying birds, making them more vulnerable to infections by various microorganisms (Holt, 2003). Onbaşılar & Erol (2007) asserted that fasting, because it causes severe physiological stress, is the least suitable method of molting in terms of bird welfare.…”
Section: Experimental Infection Of Salmonella Enteritidis In Quails Smentioning
confidence: 99%
“…The stress caused by fasting increases corticosterone plasma levels (Webster, 2003), and stress hormones are known to have anti-inflammatory properties, which reduce the effectiveness of the immune system in fighting diseases (Golden et al, 2008). Thus, birds with compromised immune system become susceptible to microorganisms, such as Salmonella Enteritidis (Holt, 2003), and may produce contaminated eggs (Gama et al, 2003), compromising public health.…”
Section: Introductionmentioning
confidence: 99%